Clinical cell therapy imaging using a perfluorocarbon tracer and fluorine‐19 MRI. Issue 6 (December 2014) - Ahrens, Eric T.; Helfer, Brooke M.; O'Hanlon, Charles F.; Schirda, Claudiu
<x xml:space="preserve">Abstract</x> Purpose Cellular therapeutics are emerging as a treatment option for a host of serious human diseases. To accelerate clinical translation, noninvasive imaging of cell grafts in clinical trials can potentially be used to assess the initial delivery and behavior of cells. Methods The use of a perfluorocarbon (PFC) tracer agent for clinical fluorine‐19 (19F) MRI cell detection is described. This technology was used to detect immunotherapeutic dendritic cells (DCs) delivered to colorectal adenocarcinoma patients. Autologous DC vaccines were labeled with a PFC MRI agent ex vivo. Patients received DCs intradermally, and 19F spin‐density‐weighted MRI at 3 Tesla (T) was used to observe cells. Results Spin‐density‐weighted 19F images at the injection site displayed DCs as background‐free "hot‐spot" images. 19F images were acquired in clinically relevant scan times (<10 min). Apparent DC numbers could be quantified in two patients from the 19F hot‐spots and were observed to decrease by ∼50% at injection site by 24 h. From 3T phantom studies, the sensitivity limit for DC detection is estimated to be on the order of ∼105 cells/voxel in this study. Conclusion These results help to establish a clinically applicable means to track a broad range of cell types used in cell therapy. Magn Reson Med 72:1696–1701, 2014. © 2014 The Authors. Magnetic Resonance in Medicine Published by Wiley Periodicals, Inc. on behalf of International Society of Medicine in Resonance.